TINGKAT KEBISINGAN DI INDUSTRI PENGGERGAJIAN KAYU STUDI KASUS DUA PENGGERGAJIAN KAYU DI KALIMANTAN SELATAN - Soenarno Soenarno; Maman Mansyur Idris (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Wood processing in Indonesia, especially sawmilling industries have been increased in the last decade. Until 1985, about 295 sawmilling industries with the production capacity of more than 8,500,000 m3/year have been installed. These industries have contributed to Indonesian foreign exchange of US 1,800.37 million. In their operations the problem of ergonomics, such as high noise levels has not considered yet.An investigation was conducted in two saw milling industries in South Kalimantan with the results as follows :Noise level in the second industry was varied from 96 to 102 dB(A), and in the first industry was ranged from 92 to 94 dB(A). This difference is due to differences in the machine lay out and working space design. Both levels are higher than the maximum tolerable noise level of 85 dB(A).Noise protection means for workers in the first industry are not required for the time being, but in the second industry they are strongly recommended.